Comparison of efficacy of mulligan's mobilization with movement with maitland mobilization along with conventional therapy in the patients with knee osteoarthritis: A randomized clinical trial - Aniqa Kiran; Muhammad Ijaz; Muhammad Qamar; Ayesha Basharat; Akhtar Rasul; Waqas Ahmed (Libyan International Medical University Journal)
Objective: The objective of this study is to determine the outcome and efficacy of Mulligan's mobilization with movement (MWM) with Maitland mobilization along with conventional therapy in the patients with knee osteoarthritis (OA). Materials and Methods: A randomized controlled trial study was performed at the Department of Physiotherapy, Mayo Hospital, Lahore, Pakistan. Sixty-two patients were selected for the study. MWM was introduced in half of the patients and Maitland mobilizations in the second half for 2 weeks. The goniometry, visual analog scale (VAS), knee range of motion (ROM), and Western Ontario McMaster OA (WOMAC) Index for knee OA were the assessment tools used to assess all patients before and after 2 weeks of intervention. Paired sample t-test was used for analysis of results. Results: The mean pre- and postdifferences in MWM group were 4.06 ± 0.99, 10.19 ± 3.87, and 19.41 ± 7.58 for VAS, ROM flexion, and WOMAC Index, respectively, while the pre- and postmean difference values for Maitland mobilization group were 3.355 ± 1.05, 10.19 ± 5.5, and 12.28 ± 7.029 for VAS, ROM flexion, and WOMAC Index, respectively. The mean differences of both treatment interventions individually were significant and showed that both were clinically effective in treating the patients of knee OA. Conclusion: It was concluded that patients in both groups showed improvement in pain, ROM, and functions.